Cut and paste pedagogy?: Academic mobility, teaching practices and the circulation of knowledge. Issue 119 (February 2021) - Liu, Tianfeng; Willis, Katie
Highlights: Academic staff often experience pedagogic dissonance when first teaching in another country. They adopt classroom and curriculum strategies to address these challenges. These strategies are shaped by their own experiences, student diversity and institutional context. Abstract: Drawing on material from qualitative research with Chinese academics in a UK university and British academics in the Chinese branch campus of that university, this paper places pedagogy at the centre of geographical debates about mobility and the internationalisation of higher education. In particular, it moves beyond the usual focus on the mobility of pedagogy in schools or the teaching of international students in higher education to consider how pedagogic practices are embodied in mobile academic staff, within particular classroom and wider institutional environments. These individuals bring their prior experience of teaching and institutional cultures to a new environment where they come up against approaches and pedagogic practices which may clash with their beliefs about good teaching. This pedagogic dissonance may create feelings of frustration or insecurity, but may also provide opportunities for creativity and self-reflection. The paper focuses on three aspects of pedagogic practice: classroom interactions, language and assessment. The focus on the embodied nature of pedagogic practice extends geographical debates around academic mobility, hierarchies of knowledge, and the internationalisation of higher education.